2020
DOI: 10.1519/jsc.0000000000003705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Augmented Feedback on Velocity Performance During Strength-Oriented and Power-Oriented Resistance Training Sessions

Abstract: Effect of augmented feedback on velocity performance during strength-oriented and power-oriented resistance training sessions. J Strength Cond Res 36(6): 1511-1517, 2022-This study examined the effects of providing instantaneous velocity feedback (knowledge of results [KR]) on velocity maintenance across multiple sets during strength-oriented and power-oriented resistance training (RT) sessions. Seventeen men completed 2 strength-oriented RT sessions (4 sets of 5 repetitions at 75% of 1 repetition maximum [1RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Subjects received velocity performance feedback immediately after completing each repetition to encourage them to perform all repetitions at the maximal intended velocity. 11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects received velocity performance feedback immediately after completing each repetition to encourage them to perform all repetitions at the maximal intended velocity. 11…”
Section: Methodsmentioning
confidence: 99%
“…7,8 In addition, providing velocity feedback during resistance training may enhance certain psychological traits, such as competitiveness or motivation, 9 which in turn may enhance mechanical performance in the short and long term. 10,11 Taking into consideration the encouraging practical applications of VBT, it is not surprising that previous studies [12][13][14] have found comparable or superior training adaptations after a VBT program in comparison with a traditional percentage-based training program (i.e. the load is prescribed from a previously established 1RM), even with a significant reduction in total training volume 13 or training stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that receiving KR can enhance athlete's performance during training, which optimises neuromuscular stimuli for training adaptation 4 . Indeed, instantaneous feedback on movement speed has been shown to acutely improve power and strength-oriented performances 4,7,8 , although the acute effect of KR on sprint performance is still unclear. Improvement in sprint performance has been reported as a result of chronic physical training when supplemented with KR 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, running demands in team sports are often non-linear, with sprints involving varying curvatures 9 . In addition, most studies that examined the acute effect of KR incorporated performance measures using single-effort, explosive movements 4,7,8 . Doma, Engel, Connor and Gahreman 10 recently examined the acute effect of KR via the provision of swim speed which resulted in faster completion times during a repeated sprint swim protocol amongst competitive swimmers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation